THE COMPONENT OF 4A AS A SUPPORT FOR INTEREST IN VISITING THE CITY OF KEDIRI, EAST JAVA - Kurniawan, Brahma Wahyu; Suaidah, Imarotus; Astuti, Indah Yuni (Transpublika Publisher, 2023)
The objective of this study is to assess how the 4A components (Amenities, Ancillaries, Accommodation, Attraction) play a role in influencing visitor interest and contributing to the growth of tourism in Kampung keren Kediri. A quantitative research approach was employed, and data were gathered from 270 tourists in Kampung keren Kediri using incidental sampling. Data analysis was carried out using Structural Equation Model (SEM) analysis. The findings of the study reveal that (1) amenities do not exert an impact on visitor interest, (2) ancillaries do not affect visitor interest, (3) accommodation does not influence visitor interest, (4) amenities do not play a role in attracting visitors, (5) ancillaries have a significant impact on attraction, (6) accommodation contributes to attraction, and (7) attraction significantly influences visitor interest. Based on these results, it is recommended that all aspects of the 4A components must be adequately addressed to enhance the chances of attracting tourists, ultimately leading to a positive economic impact, particularly benefiting the residents of Kediri City. Therefore, active engagement and cooperation among all stakeholders, from local to higher levels, are vital for the development of tourism areas.